PERBANDINGAN MODEL PEMBELAJARAN SCAFOLDING DAN ARTIKULASI TERHADAP KECAKAPAN HIDUP DENGAN MEMPERHATIKAN EMOTIONAL QUESTION SISWA - Suroto Suroto; Tedi Rusman; Erzal Syahreza Aswir (Jurnal Perspektif Pendidikan, 2019)
Students who lack life skills will tend to be difficult to achieve success. This study aims to determine the comparison of life skills of students whose learning uses Scaffolding and Articulation learning models by paying attention to students' Emotional Quetions (EQ). The research method used was quasi-experimental with a comparative approach. The research design used is treatment by level. The subjects in this study were students of class VIII MTs NU 5 Sekampung East Lampung. Testing the hypothesis of this study used a two-way variance analysis formula and two independent sample t-tests. The results of this study indicate (1) There are differences in life skills between students whose learning uses the Scaffolding and Articulation models in Integrated Social Studies subjects, (2) Life skills whose learning using the Scaffolding model is higher than using the Articulation model for students who have Emotional Quetions ( EQ) is high, (3) Life skills learning using the Articulation model is higher than using Scaffolding models for students who have low Emotional Quetions (EQ), (4) There is an interaction between the use of learning models and Emotional Quetions (EQ) on life skills .